The regulation of interleukin-8 by hypoxia in human macrophages--a potential role in the pathogenesis of the acute respiratory distress syndrome (ARDS). - Hirani, N; Antonicelli, F; Strieter, R; Wiesener, MS; Ratcliffe, P; Haslett, C; Donnelly, S (2001)
BACKGROUND: The acute respiratory distress syndrome (ARDS) represents a form of severe acute inflammatory lung disease. We have previously demonstrated significantly raised interleukin-8 (IL-8) levels in the lungs of at-risk patients that progress to ARDS, and identified the alveolar macrophage as an important source of this chemokine. We wished to extend this study in a well-defined group of patients with major trauma, and to investigate potential mechanisms for rapid intrapulmonary IL-8 generation. MATERIALS AND METHODS: Patients with major trauma underwent bronchoalveolar lavage (BAL) and IL-8 levels were measured in BAL fluid by ELISA. Human macrophages were derived from peripheral blood monocytes from healthy volunteers. Rabbit alveolar macrophages were obtained from ex-vivo lavage of healthy rabbit lungs. Macrophages were culture under normoxic or hypoxic (PO2 26 mmHg) conditions. IL-8 and other proinflammatory mediator expression was measured by ELISA, northern blotting or multi-probe RNase protection assay. RESULTS: In patients with major trauma, IL-8 levels were significantly higher in patients that progressed to ARDS compared to those that did not (n = 56, P = 0.0001). High IL-8 levels negatively correlated with PaO2/FiO2 (r = -0.56, P < 0.001). In human monocyte derived macrophages hypoxia rapidly upregulated IL-8 protein (within 2 hours) and mRNA expression (within 30 mins). Acute hypoxia also increased rabbit alveolar macrophage IL-8 expression. Hypoxia increased DNA binding activity of AP-1 and C/EBP but not NF-kappaB. Hypoxia induced HIF-1 expression, but cobaltous ions and desferrioxamine did not mimic hypoxic IL-8 induction. Hypoxia downregulated a range of other proinflammatory mediators, including MCP-1 and TNF-alpha. Both the pattern of cytokine expression and transcription factor activation by hypoxia was different to that seen with endotoxin. CONCLUSIONS: Rapidly raised intrapulmonary IL-8 levels are associated with ARDS progression in patients with major trauma. Acute hypoxia, a clinically relevant stimulus, rapidly and selectively upregulates IL-8 in macrophages associated with a novel pattern of transcription factor activation. Acute hypoxia may represent one of potentially several proinflammatory stimuli responsible for rapid intrapulmonary IL-8 generation in patients at-risk of ARDS.